2014
DOI: 10.1038/ng.2983
|View full text |Cite
|
Sign up to set email alerts
|

Whole-genome sequencing and comprehensive molecular profiling identify new driver mutations in gastric cancer

Abstract: Gastric cancer is a heterogeneous disease with diverse molecular and histological subtypes. We performed whole-genome sequencing in 100 tumor-normal pairs, along with DNA copy number, gene expression and methylation profiling, for integrative genomic analysis. We found subtype-specific genetic and epigenetic perturbations and unique mutational signatures. We identified previously known (TP53, ARID1A and CDH1) and new (MUC6, CTNNA2, GLI3, RNF43 and others) significantly mutated driver genes. Specifically, we fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

76
958
5
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 917 publications
(1,044 citation statements)
references
References 71 publications
76
958
5
5
Order By: Relevance
“…27 In this study, we used a novel FGFR2b primary antibody to predict gene amplification by immunohistochemistry and found FGFR2b overexpression in 4% of gastric cancers, and 92% of these cases were confirmed to be FGFR2 gene amplified by FISH, confirming that it is the FGFR2b isoform, and not the FGFR2c isoform, predominantly expressed in FGFR2-amplified gastric cancer. 11 We found an excellent correlation between immunohistochemistry and FISH results.…”
Section: Discussionmentioning
confidence: 64%
“…27 In this study, we used a novel FGFR2b primary antibody to predict gene amplification by immunohistochemistry and found FGFR2b overexpression in 4% of gastric cancers, and 92% of these cases were confirmed to be FGFR2 gene amplified by FISH, confirming that it is the FGFR2b isoform, and not the FGFR2c isoform, predominantly expressed in FGFR2-amplified gastric cancer. 11 We found an excellent correlation between immunohistochemistry and FISH results.…”
Section: Discussionmentioning
confidence: 64%
“…However, in this case, the underlying family predisposing gene was CTNNA1 and not CDH1 [39], and somatic mutations at LMTK3, MCTP2, MED12, PIK3CA, and ARID1A genes have been demonstrated, as well as mutations in other genes recently shown to be part of the molecular signatures of sporadic GC [54][55][56][57][58][59]. Similar studies in a series of HDGC caused either by CDH1 or CTNNA1 germline mutations, and in different progression stages, would undoubtedly help to disclose the somatic mutation landscape of this disease.…”
Section: Other Somatic Changes In Hdgcmentioning
confidence: 99%
“…In sporadic GC, p53 nuclear overexpression by IHC, was found both in intestinal and diffuse GCs and was correlated with tumour progression, poor prognosis and unfavourable response to therapy [84][85][86][87][88][89]. Moreover, NGS studies have identified TP53 mutations as one of the most frequently alterations in GCs, and TP53 has been pointed as a candidate driver gene, especially in intestinal-type GC [54,[56][57][58]90]. The evidence of p53 nuclear accumulation in our study suggests that TP53 may be a key gene involved in GC progression, also in the hereditary setting.…”
Section: New Insights In Morphological Immunohistochemical and Genetmentioning
confidence: 99%
“…Gastric cancer driver genes were obtained from 3 sources: (1) 16 gastric cancer‐related driver genes from Catalogue of Somatic Mutations in Cancer (COSMIC) Cancer Gene Census(v78)31; (2) 175 driver genes of gastric cancer from the Integrative Onco Genomics (IntOGen) database32; (3) 108 significantly mutated genes (SMGs) and 26 somatic copy number alteration genes from previously published Whole Genome Sequencing (WGS) or Whole Exome Sequencing (WES) articles 4, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22…”
Section: Methodsmentioning
confidence: 99%
“…Some of these driver genes are previously known cancer genes (eg, TP53 , ARID1A, and CDH1 ), while the others are new‐found significantly mutated genes in gastric cancer (eg, MUC6 , CTNNA2 , GLI3, and RNF43 ) 4, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22. Moreover, the copy number changes and characteristic mutational signatures also play important roles in gastric cancer development 4, 16, 17, 18, 19…”
Section: Introductionmentioning
confidence: 99%